Prevalence of Nutritional and Lifestyle-Related Risk Factors Among Young Adults: A Health Screening Study - Gopal Krishna Purohit; Swadhin Palo (Public Health, 2026)
Early assessment of health modes is crucial in young adults (ages 18–25 years), who experience a critical period of health changes and risk exposure. Screening programs in institutions allow preventive health interventions in this population. Health status, lifestyle patterns, and risk indicators of college students in a screening program at Healthcare Private Limited, Bhubaneswar. A cross-sectional health screening was performed among students aged 18–25 years using a structured nine-section Healthcare & Wellness Assessment Format that included demographics, medical history, sleep patterns, physical activity, nutrition, mental health, lifestyle risks, awareness of preventive care, and clinical parameters. The health measurements assessed were blood pressure, pulse rate, body temperature, oxygen saturation (SpO₂), height, weight, and body mass index (BMI), blood glucose test, respiratory rate measurement, hemoglobin level in the blood sample analysis, urine test, and vision tests. Measurements were obtained using standardized instruments. Screening detected differences in nutritional status, lifestyle habits, and clinical parameters. Underweight and overweight BMI categories were also detected. Mild anemia and borderline high blood pressure were observed among the students. Lifestyle factors involved poor sleep, consistently lower physical activity levels, irregular diet, and screen time. The knowledge of preventive healthcare approaches was moderate. The results emphasize the value of health screening programs in the early detection of modifiable risk factors. Instead, institutional wellness assessments may be modelled on preventive healthcare strategies to convey health optimization and early intervention